Moderate-to-severe eosinophilia induced by treatment with immune checkpoint inhibitors: 37 cases from a national reference center for hypereosinophilic syndromes and the French pharmacovigilance database. (1st January 2020) - Scanvion, Quentin; Béné, Johana; Gautier, Sophie; Grandvuillemin, Aurélie; Le Beller, Christine; Chenaf, Chouki; Etienne, Nicolas; Brousseau, Solenn; Cortot, Alexis B.; Mortier, Laurent; Staumont-Sallé, Delphine; Morschhauser, Franck; et al.
ABSTRACT: A better understanding of immune-related adverse events is essential for the early detection and appropriate management of these phenomena. We conducted an observational study of cases recorded at the French reference center for hypereosinophilic syndromes and in the French national pharmacovigilance database. Thirty-seven reports of eosinophilia induced by treatment with immune checkpoint inhibitors (ICIs) were included. The median [range] time to the absolute eosinophil count (AEC) peak was 15 [4─139] weeks. The median AEC was 2.7 [0.8─90.9] G/L. Eosinophil-related manifestations were reported in 21 of the 37 cases (57%). If administered, corticosteroids were always effective (n = 10 out of 10). Partial or complete remission of eosinophilia was obtained in some patients not treated with corticosteroids, after discontinuation (n = 12) or with continuation (n = 4) of the ICI. The AEC should be monitored in ICI-treated patients. If required by oncologic indications, continuation of ICI may be an option in asymptomatic hypereosinophilic patients, and in corticosteroid responders.